A Bibliometric Review of The B40 Households Group in Malaysia - Abdul Nasir, Nurul Nadzirah (Journal of Social Transformation and Regional Development, 2024)
To give a comprehensive assessment of the B40 household groups research sector, a bibliometric analysis of 246 papers from the Scopus data between 2029 and 2023 is being conducted by this project. The study aims to learn about the latest research topics being worked on by researchers, examine Malaysia’s contribution to the field, highlight author, university, and country collaborations in the field, and identify the most influential authors, universities, nations, and citations. Based on the study, Malaysia, the US, and the UK are the top three countries that have looked at B40 household groups. Focusing on B40 family groups most of the researchers at Universiti Kebangsaan Malaysia, Universiti Teknologi MARA, and Universiti Malaya. On this subject, Sani, N.S. is the most well-known author. Due to its unique demographic of B40 people, Malaysia is the only country in the world that carries out extensive research on B40 household groupings.